Peridotite weathering is the missing ingredient of Earth’s continental crust composition - Andreas Beinlich (Nature Portfolio, 2018)
The concentration of Ni and Cr of the continental crust cannot be explained by formation models involving differentiated magmatic rocks. Here, the authors show that hydrothermal alteration and chemical weathering of ultramafic rock compensates for the low Ni and Cr concentrations of island arc-type magmatic rocks.